A peer-led dental education program for modifying oral self-care in Mexican children - María del Carmen Villanueva-Vilchis; Jolanta Aleksejuniené; Benjamín López-Núñez; Javier de la Fuente-Hernández (Instituto Nacional de Salud Pública, 2019)
Objective. To compare peer-led dental education (PLDE) versus conventional dental instruction (CDI) in modifying children's oral self-care. Materials and methods. The intervention group (two schools) received PLDE and the control group (two schools) received CDI. The quality of oral self-care practice (OSC-P) and oral self-care skills (OSC-S) were indicated by dental plaque levels (%) and compared before and after dental education. Results. There were no baseline OSC-P differences between the control (55.8 ± 12.8%) and intervention (55.5 ± 14.6%) groups or OSC-S differences between the intervention (38.5 ± 13.2%) and control (38.1 ± 12.5%) groups. At the three-month follow-up we observed OSC-P deterioration in the control group (63.2 ± 15.0%) and OSC-P improvement in the intervention group (52.2 ± 15.6%). The OSC-P/OSC-S regression models found these predictors: baseline oral self-care, group affiliation, and mother's education (p<0.05). Conclusion. The hypothesis was confirmed and significant predictors were baseline oral self-care levels, group affiliation, and mother's education.